Implementation of youtube as a learning media in the new normal era - Dahlan Abdullah; Achmad Harristhana Mauldfi Sastraatmadja; Nana Citrawati Lestari; Nanda Saputra; Gamar Al Haddar (Institute of Computer Science (IOCS), 2023)
The world of education must be able to adjust to new typical conditions, such that some schools use online learning, blended learning, and face-to-face instruction. Currently, the transition period from pandemic to new normal is known as the period of adjusting government policies and the management capabilities of each school, so that in the transition of this condition in the world of education, it is necessary to change learning procedures, including the original learning media. Internet is a technological innovation that can be utilized to facilitate distance learning. The internet facilitates human communication, information access, and entertainment. YouTube, which is a social media network but also has advantages as a learning medium, is one of the most popular platforms. The objective of this research is to investigate and assess the current application of YouTube as a learning medium in the new normal era. The research technique employs a literature review of YouTube's implementation and usage as a learning medium in order to create an analysis of YouTube's implementation and use from the perspectives of educators and students at varying levels of education in order to facilitate learning.